Alternative treatment method for crimean congo hemorrhagic fever: coupled plasma filtration and adsorption - Dilşat TEPE; Gürdal YILMAZ; Ahmet Oğuzhan KÜÇÜK; Mehtap PEHLİVANLAR KÜÇÜK (Journal of Global Antimicrobial Resistance)
AIM: This report aims to present the use of Coupled Plasma Filtration and Adsorption(CPFA) in CCHF patients. BACKGROUND: Crimean-Congo Hemorrhagic Fever(CCHF) is a viral hemorrhagic fever syndrome that can cause multi-organ failure with hyperactivation of the immune system. There is no proven treatment for CCHF,supportive care is essential for management.Extracorporeal depurative techniques have been used to remove inflammatory mediators from the bloodstream. RESULTS: We performed CPFA on three patients with CCHF, all of which were confirmed with PCR.A 35-year-old female was admitted one week after tick-exposure.Despite supportive treatment, patient developed mucosal and gastrointestinal bleeding due to disseminated intravascular coagulation(DIC).After CFPA,her clinic situation and laboratory results improved.A 54-year-old female was admitted to the Intensive Care Unite due to severe bleeding and had a history of tick bite nine-days-ago. She had multiple organ failure with DIC,we started CPFA.Patient didn't respond to the treatment and died.A 69-year-old male was admitted to the hospital on the seventh-day of exposure to tick. He had diabetes, hypertension and coronary artery disease.Next day,patient developed alveolar hemorrhage and his liver enzymes,coagulation parameters deteriorated.We performed CFPA,however,the patient didn't respond to treatment and died. CONCLUSION: We suggested that CPFA may have positive effects on the outcome and prognosis of critically ill CCHF patients.Only one patient responded well which can be a result of being young, early admission to the hospital and lack of comorbidity.CPFA may be an option to treat severe CCHF infection with cytokine storm.However,there is a need for further studies on when we should apply this treatment and whether early application prevents mortality.